Empowering Career Choices: Developing Social and Emotional Support Services for Adolescents - Mukhlinatus Sangadah; Mudafiatun Isriyah; Weni Kurnia Rahmawati (Jurnal Bimbingan dan Konseling Terapan)
Adolescence is a critical developmental phase where career decision-making plays a pivotal role in shaping individuals’ economic stability, personal fulfillment, and societal contributions. This research addresses the challenges adolescents face in career planning, particularly in Indonesia, where structured career counseling frameworks are limited. Existing approaches often neglect the emotional and social dimensions of decision-making, resulting in increased career indecision and misalignment between aspirations and opportunities. While global research highlights the transformative potential of integrating social and emotional support into career counseling, these practices remain underdeveloped in Indonesian educational settings This study aims to fill this gap by developing a context-specific counseling module tailored to Indonesian high school students. Employing a Research and Development (R&D) methodology, the study integrated self-assessment tools, emotional regulation strategies, and goal-setting guidelines to address cognitive and emotional barriers in career decision-making. The module was validated through expert reviews and field testing with high school students, achieving high ratings for its relevance, clarity, and usability. The findings reveal significant improvements in students’ confidence, decision-making skills, and career readiness, underscoring the effectiveness of incorporating social and emotional competencies in career counseling. The research contributes to theoretical discourse by applying Social Cognitive Career Theory and Trait and Factor Theory to explore the interplay between individual attributes and environmental factors in career development. While the study demonstrates promising outcomes, it acknowledges limitations, such as its focus on a specific population and the absence of longitudinal assessments. The research provides a scalable framework that bridges critical gaps in Indonesian career counseling and offers valuable insights for global applications in similar contexts.